Impact of Job Satisfaction on Organizational Citizenship Behaviour Mediated by Organizational Commitment in Public Sector Banks - et. al., Anand Karuna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this paper is to investigates the extent that impact of job satisfaction on organizational citizenship behaviour mediated by organizational commitment in public sector banks. In past decades organizational citizenship behaviour developed a significant concept in the field a of management and psychology and established an inordinate transaction of consideration in the literature. Job satisfaction is an essential aspect of employee performance and success. Employees who are satisfied will go much beyond their job roles and this will improve organizational effectiveness. The sample size is 309 and data was collected from public sector bank employees through questionnaire. Correlation and regression analysis both were used to test the hypotheses in this study. All the present variables in this research were found to be expressively associated with each other.